(untitled) (Bangladesh Journal of Medical Science, 2026)
Antimicrobial resistance is a significant global health challenge, driven in part by the overprescription of antimicrobial agents and their improper use by patients. This study aimed to compare the antimicrobial properties of five desert plants—Indigofera intricata, Plantago psyllium, Tribulus arabicus, Fagonia indica Burm.f., and Zygophyllum shewinf—alongside various types of honey, olive oil, and colostrum against select Gram-positive and Gram-negative bacteria and fungi. The objective was to associate their antimicrobial activity with their phenolic and triterpenoid profiles. Each plant material was extracted using solvents of different polarities, and thin-layer chromatography was employed for phytochemical analysis. The total phenolic and flavonoid contents of the extracts were also measured, and the purity of the honey samples was evaluated. Antimicrobial activity was assessed using both well diffusion and dilution methods. The findings revealed that the plant extracts, different honey varieties, olive oil, and colostrum all demonstrated varying levels of antimicrobial efficacy. BJMS, Vol. 25 No. 01 January’26 Page : 184-195